Multidimensional poverty and inequality of opportunity in Peru: taking advantage of the longitudinal dimension of Young Lives - Escobal, J (Young Lives, 2012)
Multidimensional poverty and inequality of opportunity are closely interconnected concepts. Equality of opportunity levels the playing field so that circumstances such as gender, ethnicity, geographical location or family background, which are beyond the control of a child, do not influence his or her life chances. This means that if equality of opportunity is achieved, a child will be able to overcome multidimensional poverty and deprivation. Using the information collected in Peru during the first two rounds of the Young Lives longitudinal study, we describe how multidimensional poverty and inequality of opportunity evolve as children get older. Results show that although scalar indices of multidimensional poverty, deprivations or inequality of opportunity may be quite useful as an advocacy tool, they may mask important heterogeneities.